Unfitting construction practicing in individual buildings: Lack of Technical Standards and Architectural defects: Reasons and act for improvement - Galeb, Ahmed (Thamar University Journal of Natural & Applied Sciences, 2023)
Yemen has developed widely in the construction of buildings like the rest of the world, but the process of conducting is still suffering a lot of unfitting construction practicing and encroachments, in addition it has some flaws and various operational disadvantages which affect it negatively upon several aspects four of the most important are: architectural, construction, economically and environmentally. Actually In real life and widely prevailed in Yemen, a very large percentage of “houses of the individuals " buildings are conducted improvisational and very far from the standards and criteria to be followed in the implementation of buildings in correct operational steps. This study aim to show identify the missing link between the theoretical bases for construction and the actual implementation methods and highlighted defects based on this wrong method adopted in Yemen recently. In addition it shows the far distance it is from standards and wrong usage of materials in the construction of buildings. An incorrect construction method described. Finally, the research concluded the shortcoming, and suggests scientific steps to improve construction performance in order to avoid the current defects in the future.